A bowl-shaped phenoxido-bridged binuclear zinc complex: experimental and theoretical studies - Azam, Mohammad; Velmurugan, Gunasekaran; Trzesowska-Kruszynska, Agata; Al-Resayes, Saud I.; Kruszynski, Rafal; Venuvanalingam, Ponnambalam (Inorganica chimica acta, 2022)
A new dinuclear zinc coordination complex with di(μ-alkoxido) bridge obtained from [[H2L = N,N-(salicyaldene)-1,3-diaminopropan-2-ol] was investigated by IR, 1H- & 13C NMR spectroscopy. Single crystal X-ray analysis reveals that the Zn1 atom in the title complex is five coordinated and bound to two alkoxide atoms, two nitrogen atoms, and a chloride ion at apical position in distorted square pyramid geometry, while the second central cation, Zn2, is four coordinated and its O2Cl2 coordination environment is distorted tetrahedral. The single-crystal X-ray crystallographic measurements and DFT calculations reveal that the complex has a bowl-like structure. Hirschfeld surface analysis, energy frameworks QTAIM, NBO, and EDA analyses show clearly that the structure contains a variety of classical and non-classical interactions that help to extend the crystal net dimension. TGA is used to investigate the stability of the structure of the title complex.
Gesehen am 13.05.2022